2014
DOI: 10.1063/1.4896362
|View full text |Cite
|
Sign up to set email alerts
|

Deep hole injection assisted by large V-shape pits in InGaN/GaN multiple-quantum-wells blue light-emitting diodes

Abstract: We investigated the hole injection mechanism in InGaN/GaN blue light-emitting diodes by growing monolithic dual-wavelength multiple-quantum-wells and measuring the electroluminescence spectra at different current densities under room temperature. By analyzing the spectral competition from quantum wells at different vertical locations, the hole injection depth was quantitatively measured. During the epitaxial growth, large size V-shape pits with 200–330 nm diameter were intentionally formed in the active region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…In the case of electrical injection, holes from the p-GaN layer are directly (path 1) or indirectly (path2) injected into the A-QWs in the direction of the potential energy minimum and undergo radiation recombination with the electrons, as depicted in Figure (f). In other words, the presence of V-pits provides a special path for readier holes to bypass the top QWs near the p-side, and the sandwich designed active region offers a subtle use of these “disadvantages”. We believe that the sandwiched A-QWs have a smaller ground-state energy level, which can induce and limit carrier recombination primarily in the A-QWs.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the case of electrical injection, holes from the p-GaN layer are directly (path 1) or indirectly (path2) injected into the A-QWs in the direction of the potential energy minimum and undergo radiation recombination with the electrons, as depicted in Figure (f). In other words, the presence of V-pits provides a special path for readier holes to bypass the top QWs near the p-side, and the sandwich designed active region offers a subtle use of these “disadvantages”. We believe that the sandwiched A-QWs have a smaller ground-state energy level, which can induce and limit carrier recombination primarily in the A-QWs.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Such a phenomenon should be attributed to the facilitation of deep hole injection assisted by the large V-pits, as shown in Figure 2 c,d. The V-pits make the current bypass the top QWs and directly inject into the deeper QWs [ 33 , 34 ]. With the ascending current, the bypass effect is weakened, hence leading to the enhancement of the top QWs’ emission, i.e., the green emission.…”
Section: Resultsmentioning
confidence: 99%
“…Cho et al found that the NR can be suppressed effectively when the energy barrier height is larger than about 80 meV . These researches indicate that V-shaped pits can significantly improve IQE, and several groups , have conducted plenty of thorough studies on the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…By growing InGaN/GaN blue MQWs and measuring the electroluminescence spectra, Li et al investigated the effect that the V-shaped pits have on hole injection. 31 They found that the large V-shaped pits are of great importance for the hole injection depth. By numerical simulation, Quan et al reported that V-shaped pits can promote hole injection and thus enhance the optical performance of the GaN-based MQWs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation